2005
DOI: 10.1086/426605
|View full text |Cite
|
Sign up to set email alerts
|

How Warnings about False Claims Become Recommendations

Abstract: Telling people that a consumer claim is false can make them misremember it as true. In two experiments, older adults were especially susceptible to this "illusion of truth" effect. Repeatedly identifying a claim as false helped older adults remember it as false in the short term but paradoxically made them more likely to remember it as true after a 3 day delay. This unintended effect of repetition comes from increased familiarity with the claim itself but decreased recollection of the claim's original context.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
265
1
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(286 citation statements)
references
References 25 publications
13
265
1
7
Order By: Relevance
“…This "illusion of truth" was stronger for older adults than younger adults. Although Skurnik et al 33 did not measure affective responses to the claims, their findings are consistent with the notion that the affect associated with the mere (even subliminal) exposure to stimuli can influence preferences.34 , 35 Older adults may tend to forget important message details, relying instead on how they feel about the message to determine their evaluations and choices. The affect coming from the positive feelings of familiarity created by mere exposure to the message is less helpful information than the content of the message (at least in this case where the health claims are false).…”
Section: Feelings As Informationmentioning
confidence: 68%
“…This "illusion of truth" was stronger for older adults than younger adults. Although Skurnik et al 33 did not measure affective responses to the claims, their findings are consistent with the notion that the affect associated with the mere (even subliminal) exposure to stimuli can influence preferences.34 , 35 Older adults may tend to forget important message details, relying instead on how they feel about the message to determine their evaluations and choices. The affect coming from the positive feelings of familiarity created by mere exposure to the message is less helpful information than the content of the message (at least in this case where the health claims are false).…”
Section: Feelings As Informationmentioning
confidence: 68%
“…to understand the interplay between the two systems' processing features on the truth effect itself (and not memory's role in it), it is preferable to use manipulations that only distinguish between system 1 and system 2 at the moment when truth judgments are made. few experiments have done this, and those that have only did so indirectly, either by including older adults in the samples (e.g., skurnik, yoon, park, & schwarz, 2005) or delaying the interval between the familiarization and truth evaluation phases (e.g., bacon, 1979;brown & nix, 1996;garcia-marques, silva, Reber, & Unkelbach, 2015;hasher et al, 1977;hawkins & hoch, 1992;skurnik et al, 2005). these studies also showed that illusions of truth are not dependent on explicit memory because delaying the truth evaluation up to a month (e.g., brown & nix, 1996) did not eliminate the effect; in some cases, it even boosted it (e.g., hawkins & hoch, 1992).…”
Section: The Dual-process Account Of the Illusion Of Truth Effectmentioning
confidence: 99%
“…The first is the degree of false beliefs espoused by many participants and the fact that they are reinforced by the media and politicians (see Every & Augoustinos, 2008). In one study, it was found that if you consistently hear something, false or otherwise, you are much more likely to remember it (Skurnik, Yoon, Park, & Schwarz, 2005). In the Skurnik et al (2005) study, participants were told that information was false.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…In one study, it was found that if you consistently hear something, false or otherwise, you are much more likely to remember it (Skurnik, Yoon, Park, & Schwarz, 2005). In the Skurnik et al (2005) study, participants were told that information was false. In the short term, they remembered this correctly.…”
Section: Practical Implicationsmentioning
confidence: 99%